FEMINISME DALAM NERACA (Perspektif Islam) - Untung, Moh. Slamet (MUWAZAH, 2009)
In female perspectives, there are assumptions of strains caused by dramatized biological differences. Therefore, they stipulate the need of scientific to find the psychological differences among males and females. Their spirit in finding those answers resulting on some movements, for instance emancipation, feminism or females freedom, leading to one point: giving same right, chances and responsibility among males and females. The root of feminism basically has already existed since the 19th century. That movement has developed in some countries, not only in United States of America but also in Western Europe, Japan and some Islam dominated countries which the laters are claimed by western as the tormenter of females while in reality Islam is proven as the reverse one.